2010
DOI: 10.1590/s1980-65232010000400009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two models of stress associated with ligature-induced periodontitis on hematological parameters in rats

Abstract: Purpose: To evaluate the effect of two models of chronic stress in rats and their association with induced periodontitis on hematological parameters: mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), hematocrit (Ht), erythrocytes (Hm), hemoglobin (Hg) and leukocytes (Lk). Methods: Forty-eight adult Wistar rats were randomly distributed into four groups (n=12): physical stress (PSG), variable stress (VSG), ligature (LG) and control (CG) and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…Similar to our studies, others have shown decreases in WBC and RBC counts in animals exposed to immobilization stress [ 18 ]. Some studies reported that immobilization changes in blood parameters such as Hb, HCT, MCV, MCH, and MCHC [ 19 ], but in this study no statistical differences were observed in these parameters. The increase in the hematological constituents in the stress loaded group cotreated with SP might be due to the antioxidant, antilipid peroxidation, and anticonvulsant effects of SP.…”
Section: Discussioncontrasting
confidence: 80%
“…Similar to our studies, others have shown decreases in WBC and RBC counts in animals exposed to immobilization stress [ 18 ]. Some studies reported that immobilization changes in blood parameters such as Hb, HCT, MCV, MCH, and MCHC [ 19 ], but in this study no statistical differences were observed in these parameters. The increase in the hematological constituents in the stress loaded group cotreated with SP might be due to the antioxidant, antilipid peroxidation, and anticonvulsant effects of SP.…”
Section: Discussioncontrasting
confidence: 80%
“…Since women were more predisposed to iron-deficiency anemia than men, which might lead to a sex difference in the presentations of erythrocyte indices that women were more likely to have a lower hematocrit and hemoglobin level. On the other respect, those young adults with localized periodontitis and greater BMI in the present study might experience higher physical stress while on regular exercise training, which has been observed with an increase of erythrocyte indices in an animal model [ 37 ]. Based on these evidence mentioned above, we acknowledged that the relationships between erythrocyte indices and periodontitis should be interpreted carefully, which might vary by the stage of periodontitis, BMI and levels of physical activity or fitness of the study population.…”
Section: Discussionmentioning
confidence: 92%